2014
DOI: 10.1002/anie.201405664
|View full text |Cite
|
Sign up to set email alerts
|

Crowning Proteins: Modulating the Protein Surface Properties using Crown Ethers

Abstract: Crown ethers are small, cyclic polyethers that have found wide-spread use in phase-transfer catalysis and, to a certain degree, in protein chemistry. Crown ethers readily bind metallic and organic cations, including positively charged amino acid side chains. We elucidated the crystal structures of several protein-crown ether co-crystals grown in the presence of 18-crown-6. We then employed biophysical methods and molecular dynamics simulations to compare these complexes with the corresponding apoproteins and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 25 publications
3
50
1
Order By: Relevance
“…Both K20 side chains of the wild-type protein are stabilized by electrostatic interactions with sulfates and E5′ side chains from the neighboring protein (symmetry-related molecules) in the crystal (Fig 2B). The K24 side chain is more ordered in chain A, which is stabilized by polyethylene glycol 400 (PEG 400) (Fig 1B), similar to the stabilization observed in crown ether binding mode [39]. On the other hand, the K24 side chain in chain B forms electrostatic interactions with the E39′ side chain of the neighboring protein (Fig 2C).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Both K20 side chains of the wild-type protein are stabilized by electrostatic interactions with sulfates and E5′ side chains from the neighboring protein (symmetry-related molecules) in the crystal (Fig 2B). The K24 side chain is more ordered in chain A, which is stabilized by polyethylene glycol 400 (PEG 400) (Fig 1B), similar to the stabilization observed in crown ether binding mode [39]. On the other hand, the K24 side chain in chain B forms electrostatic interactions with the E39′ side chain of the neighboring protein (Fig 2C).…”
Section: Resultssupporting
confidence: 54%
“…The extended N- or C-terminal tails of DNA-binding domains often increase the affinity for the target DNA and thus represent crucial segments for gene activation or repression [39]. Based on the FP, EM, and FRET analyses, the basic and flexible C-termini of Sso7c4 may act as two hands that grasp the DNA molecule, further inducing DNA bending.…”
Section: Resultsmentioning
confidence: 99%
“…As noted earlier, the Neisseria DMP19 dimer was first determined to be a transcriptional regulator (12). However, in a subsequent study, another conformation of DMP19 was found (39). In this newly determined structure, helices α1 and 2 of DMP19, which are both involved in the dimer formation in the original dimeric DMP19 structure, were rotated by 180 to make two DMP19 monomers that were unable to assemble into a dimer.…”
Section: Dmps That Target Bacterial Histone-like Proteinsmentioning
confidence: 79%
“…In this study,w ef irst crystallized the apo form of PigA and then the FADc omplex by adding crowne ther. [9] The XRD resolution was improved from 2.55 to 1.3 .I naddition to clearly elucidating the FAD-binding mode, the crystal structure also allows model construction of the substrate, which is carried by PigG. Based on the model, ac atalytic mechanism is proposed, in which Glu244 on the Re side of FADs tarts the reactionb y a-proton abstraction from the proline.W ea lso found ap lausible oxygen-binding site near the Si face of FAD, at which hydride transfer may be mediated by Thr160.…”
Section: Resultsmentioning
confidence: 99%
“…The crown ether can stabilize crystal packing by binding to surface lysine side chains and providing hydrophobic interactions. [9] In the end, as econd crystal form was obtained that diffracted X-rays more effectively to 1.8 and 1.3 .Itbelongstospace group I222 and contains one molecule of PigA in the asymmetric unit. The structures were refined to R/R free values of 0.143/0.174 at 1.8 and 0.114/ 0.127 at 1.3 .E ach model comprises 383 amino acid residues; one FAD; severals maller ligands, such as crown ether and ethylene glycol;a nd an umber of water molecules.T he C-terminal residues,i ncluding the His 8 -tag, were not seen.…”
Section: Introductionmentioning
confidence: 98%